ERC: A Theory of Equity, Reciprocity, and Competition - Bolton, Gary E; Ockenfels, Axel (American Economic Review, 2000)
We demonstrate that a simple model, constructed on the premise that people are motivated by both their pecuniary payoff and their relative payoff standing, organizes a large and seemingly disparate set of laboratory observations as one consistent pattern. The model is incomplete information but nevertheless posed entirely in terms of directly observable variables. The model explains observations from games where equity is thought to be a factor, such as ultimatum and dictator, games where reciprocity is thought to play a role, such as the prisoner's dilemma and gift exchange, and games where competitive behavior is observed, such as Bertrand markets. (JEL C78, C90, D63, D64, H41)